2023
DOI: 10.1111/irv.13092
|View full text |Cite
|
Sign up to set email alerts
|

Results from a test‐and‐treat study for influenza among residents of homeless shelters in King County, WA: A stepped‐wedge cluster‐randomized trial

Abstract: Background: Persons experiencing homelessness face increased risk of influenza as overcrowding in congregate shelters can facilitate influenza virus spread. Data regarding on-site influenza testing and antiviral treatment within homeless shelters remain limited.Methods: We conducted a cluster-randomized stepped-wedge trial of point-of-care molecular influenza testing coupled with antiviral treatment with baloxavir or oseltamivir in residents of 14 homeless shelters in Seattle, WA, USA. Residents ≥3 months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…We used a repeated cross‐sectional design of active respiratory virus surveillance to enroll residents and staff of homeless shelters in King County, Washington over the course of three RSV seasons from January 2019 to May 2021. Participants were enrolled through two larger studies: the Seattle Flu Study from November 2018 to May 2019, 7 and a randomized controlled trial of on‐site testing and treatment for influenza in homeless shelters 8 from November 2019 to May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…We used a repeated cross‐sectional design of active respiratory virus surveillance to enroll residents and staff of homeless shelters in King County, Washington over the course of three RSV seasons from January 2019 to May 2021. Participants were enrolled through two larger studies: the Seattle Flu Study from November 2018 to May 2019, 7 and a randomized controlled trial of on‐site testing and treatment for influenza in homeless shelters 8 from November 2019 to May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 102 articles were therefore full-text-reviewed; of them, 66 were removed from the analyses as they were not consistent with the research topic, while 3 further reports were removed for not fulfilling the inclusion criteria, and 2 reports were removed for including cases otherwise described in other studies [19][20][21]96,97]. The final sample included a total of 31 studies (0.62% of the initial sample); of them, 17 were prevalence studies [4][5][6]17,18,42,[98][99][100][101][102][103][104][105][106][107][108], 12 studies reported on the incidence of respiratory pathogens [19][20][21]44,[109][110][111][112][113][114][115][116] and the remaining 2 studies reported on the outcome of respiratory infections in HP [117,118]. As two incidence studies also included outcome data, a total of four outcome studies were ultimately retrieved [19,112].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The twelve included studies reported on data collected from January 2019 to December 2021, mostly from the USA (seven studies) [19][20][21]44,[113][114][115], followed by Canada [112,116], Italy [109,110] (two studies each) and Germany (one study) [111], for a total of 36,531 HP. However, as five papers reported on HP from Seattle and King's County [19][20][21]44,[113][114][115], while the Italian and Canadian studies reported on cases drawn from the same area, the overall number of unique individuals included in the pooled sample cannot be determined.…”
Section: Characteristics Of Incidence Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the identification of SARS-CoV-2 community transmission in Washington state on 24 February 2020 [14], the first year of the influenza trial intervention was paused on 1 April 2020 and eligibility was expanded to include all shelter staff and residents aged ≥3 months, regardless of symptoms (Supplementary Figure S1). Participants eligible for COVID-19 testing did not have to be eligible for the influenza test-and-treat intervention during the study period, but they could elect to take part during surveillance months when the intervention was available for those who met additional criteria [15].…”
Section: Study Design Overview and Populationmentioning
confidence: 99%